Trends in replacement of pacemaker leads in the Netherlands: A long‐term nationwide follow‐up study. Issue 7 (4th June 2018) - de Vries, L.M.; Leening, M.J.G.; Dijk, W.A.; Hooijschuur, C.A.M.; Stricker, B.H.; van Hemel, N.M.
Abstract: Background: Our objective was to investigate trends over time in longevity and reasons for replacement with or without extraction of pacemaker leads after first implantation. Methods: Data collected between 1984 and 2006 in the national Dutch pacemaker registry were used. This registry covered 84% of sold leads. First lead replacement with or without extraction of one or more leads implanted with a first pacemaker generator was the endpoint of interest. The time interval of and reason for first replacement were analyzed. A 7‐year follow‐up interval after first implantation was used to analyze changes over time. Results: During 22 years of data collection, 138, 225 leads were implanted with a first pacemaker generator. Within a mean 5.5 (SD 4.4) years for 7, 377 patients one or more leads were extracted for the first time. In total, 8, 849 leads (6.4%) were replaced or extracted. The main reasons for first replacement of leads with or without extraction were insulation failures (14.6%), infection (8.8%), displacement (7.6%), or for elective reasons (10.0%). The number of insulation failures peaked during 1991–1995. Conclusions: Despite improvements in pacing techniques and experience with cardiac devices, we found that insulation and conductor failures, and complications such as infections, did not diminish over the 20 years of the registry. Continuing attention in clinical practice for the evaluation of these adverse outcomes and maintaining quality registries is warranted, whereas manufacturers should use this information to further improve their devices.